RESPON PRODUKSI TANAMAN MENTIMUN (Cucumis sativus L.) DENGAN APLIKASI PUPUK ORGANIK CAIR (POC) URIN KELINCI - Nurmi, Nurmi; Napu, Samsilyanto; Dude, Suyono (Department of Agronomy, Faculty of Agriculture, University of Mataram and Indonesian Society of Agronomy, NTB Branch, 2023)
The purpose of this study was to determine the response and yield of the cucumber Cucumis sativus L.) plant to the application of rabbit urine liquid organic fertilizer (LOF). This study was conducted from January to March 2020 in Buntulia Barat Village, Sub-district of Duhidaa, District of Pohuwato, Gorontalo Province. The study used randomized completely block design (RCBD) consisting of 4 treatments i.e.: control (without LOF), LOF at the rate of 50 ml/plant, LOF at the rate of 100 ml/plant, and 1 LOF at the rate of 50 ml/plant. Each treatment was repeated 3 times. Observation of parameters included the number of fruit, the weight of fruit per plant, the fruit length, the fruit diameter, the fruit yield per hectare. Data were analyzed by the Analysis of Variance (ANOVA) followed by a least significant difference (LSD) at the 5% significant level for parameters showed significant difference by Anova test. The results of the study showed that the application of LOF had a significant effect on the height of cucumber plant at 2 weeks after planting (WAP), 3 WAP, and 4 WAP. LOF treatment of rabbit urine had no significant effect on the number of fruit, fruit weight, and fruit length, but had significant effect on the fruit weight per plant, fruit diameter, and fruit yiled per hectare. The dose of 50 ml/plant had the best effect on the yield of the cucumber plant.